Environmental Managers and Institutional Work: Reconciling Tensions of Competing Institutional Logics. Issue 2 (27th February 2017) - Dahlmann, Frederik; Grosvold, Johanne
ABSTRACT: Firms face a variety of institutional logics and one important question is how individuals within firms manage these logics. Environmental managers in particular face tensions in reconciling their firms' commercial fortunes with demands for greater environmental responsiveness. We explore how institutional work enables environmental managers to respond to competing institutional logics. Drawing on repeated interviews with 55 firms, we find that environmental managers face competition between a market-based logic and an emerging environmental logic. We show that some environmental managers embed the environmental logic alongside the market logic through variations of creation and disruption, thus over time creating institutional change, which can result in blended logics. Others, however, pursue a strategy of status quo or disengagement through maintenance or other forms of disruption, where the two logics coexist in principle but not in practice; instead the market logic retains its dominance. We discuss the implications of our findings for research.